IMPACT OF PROFITABILITY, MARKET, AND SOLVENCY RATIOS ON DIVIDEND POLICY: THE CASE OF COAL MINING COMPANIES ON THE IDX (2020–2024) - Marli, Marli; Sugiharto, Didik Priyo (Management Studies and Business Journal (PRODUCTIVITY), 2025)
The coal mining industry in Indonesia plays a vital role in meeting national energy needs and contributes significantly to the economy. However, this sector is highly vulnerable to global commodity price volatility. Dividend policy, which reflects profit distribution and signals a company’s financial health, is strongly influenced by internal financial conditions and market perceptions. This study is crucial for understanding the determinants of dividend policy amid market dynamics and challenging macroeconomic conditions during the 2020–2024 period, including the impact of the COVID-19 pandemic. This quantitative study aims to analyze the influence of profitability ratios, market value, and solvency on dividend policy in coal mining companies listed on the Indonesia Stock Exchange (IDX) during the specified period. The study uses a quantitative approach with descriptive and verification designs. Secondary data were obtained from officially published company financial statements. Data analysis was conducted using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method to test causal relationships among variables, with evaluation of the measurement model and structural model. The findings show that profitability has a positive and significant influence on dividend policy, indicating that more profitable companies tend to implement more stable and higher dividend policies. In contrast, market value shows a negative and insignificant effect, while Return on Assets (ROA) shows a marginally significant negative effect. These results confirm that profitability is the main predictor of dividend policy in this model. Profitability is the dominant factor in determining dividend payment decisions, compared to external factors such as market valuation or other profitability measures. The practical implication is that financial managers should prioritize improving profitability to optimize dividend strategies, which in turn can enhance investor confidence and company sustainability.